The Role of Brand Benefits in Financial Quality, Based on Responsiveness and Guarantee, and Its Implications for Customer Loyalty: Study of One Digital Financial Service Provider in Indonesia - Imelda Megawati (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
This study aims to examine the impact of brand benefits on a firm's financial performance. The primary emphasis is on two critical aspects of brand advantages: responsiveness and assurance. The present study additionally investigates the influence of financial quality on customer loyalty. The research methodology employed in this study entailed acquiring data from a diverse pool of respondents who served as customers for different brands within the relevant industry—the process of data collecting involved the administration of questionnaires and the execution of organized interviews. The study employed statistical research to examine the correlation between brand benefits, financial quality, and consumer loyalty. The empirical evidence suggests that the level of responsiveness and assurance exhibited by a brand has a notable influence on a firm's financial performance. Moreover, a positive correlation exists between enhanced financial quality and increased levels of consumer loyalty. The conclusions of this study suggest that firms should recognize the significance of brand responsiveness and assurance in enhancing their financial performance. This further emphasizes the significance of upholding and improving financial excellence to bolster client loyalty. The present study provides a valuable contribution to comprehending the interplay among brand benefits, financial quality, and consumer loyalty within the contemporary industry landscape.